Infallibility of the Prophets - Abdullah , Zahraa (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to Allah , prayer and peace be upon the Messenger of Allah As for after: The research included an introduction, three topics and a conclusion. The first topic included the definition of the concept of infallibility Linguistically and idiomotically and its types, with an explanation of each type in a brief way With reference to the transfered evidence (the Qur’an and the Sunnah) as well as mental evidence , As for the second topic included statements in the infallibility and discussion, as well as responding to those who deny it with discussion of any sayings . The third topic is concerned with reporting some of the stories of the prophets and messengers through the Qur’anic texts whose apparent illusion is the proportion of sins of the prophets, discussed and clarified, The research ended with a conclusion that summarized the most important results.